A Sociolinguistic Analysis of Sword Verses Through Muhammad Izzat Darwazah on Al-Tafsīr Al-Ḥadīth Tartīb Al-Suwar Ḥasb Al-Nuzūl - Ahmad Fawaid; Thoriqotul Faizah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to discuss Muhammad Izzat Darwazah’s perspective about the sword verses and the issues of its abrogation towards the peaceful verses (ayat al-silm) on al-Tafsīr al-hadīth Tartīb al-Suwar hasb al-Nuzūl. This paper focuses on the problem; how is Darwazah’s perspective on the theory of abrogation, that the peaceful verses have been abrogated by the sword verses? Furthermore, how is Darwazah’s perspective on the sword verses and its relation to the peaceful verses from a sociolinguistic perspective? Using a literary research method and a sociolinguistic approach, this article concludes that, according to Darwazah, there is no abrogation of peaceful verses by the sword verses. To prove his point, Darwazah presents the facts and conditions when the sword verses were revealed. This research also concludes that, through sociolinguistic analysis, wars/jihād never occurred during the prophet’s time except for self-defense. Furthermore, Darwazah argues that the sword verses, which are often used by Muslim extremists to legitimize their actions, have a different context from today, when inter-religious communities live peacefully.